THE SENSITIVITY TEST OF MYCOBACTERIUM TUBERCULOSIS ISOLATES FROM SUSPECT TUBERCULOSIS PATIENTS TO THE SEROMUCOUS OF SNAIL AND CHITOSAN AS AN ALTERNATIVE ANTI-TUBERCULOSIS DRUGS - SUTANTO, YUSUP SUBAGIO; SUTANTO, MAGDALENA; HARTI, AGNES SRI; PUSPAWATI, NONY (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The purpose of this research is to study the sensitivity of Mycobacterium tuberculosis (MTB) isolates from suspect TB patients to seromucous of snail and chitosan as an alternative to anti-TB drugs. Methods: The research methods include management specimen, freeze-drying of snail seromucous; formulation of dosage preparation; identification of MTB isolates; and sensitivity testing of MTB isolates to snail seromucous, chitosan, and streptomycin, isoniazid, rifampicin, and ethambutol (SIRE). Results: The characteristics of respondents by sex and age are the majority of male respondents and productive adult age that is 26 years–52 years. MTB isolates used in the study were obtained from the results of the screening of sputum samples of suspect TB patients through microscopic smear examination and molecular rapid test using GeneXpert tools. MTB isolates in patients suspect TB are resistant against seromucous of snails and chitosan that it is compared with SIRE. The dosage of snail seromucous is 8000 mg/l, chitosan 2% is 800 mg/l, and SIRE, respectively (rifampicin 8000 mg/l, isoniazid 20 mg/l, ethambutol 200 mg/l, streptomycin 800 mg/l). Conclusion: MTB isolates from patients suspect who TB is resistant to seromucous of snail (8000 mg/l) and chitosan (800 mg/l).